Has Revenues and Expenditures of Mihrişah Valide Sultan Between 1798-1805 - Temel, Eşref (Fırat University, 2022)
Mihrişah was the headwoman of Sultan Mustafa III (1757-1774) and the mother of Sultan Selim III (1789-1807) in the Ottoman State, and served as a valide sultan between 1789-1805. Mihrişah Valide Sultan became one of the people with the highest income after the sultan, thanks to the has she ran. He was introduced in the literature as "kind, benevolent and religious", and was generally discussed in the context of the foundation works he had commissioned or the charity he had done. In this study, the has income of the valide sultan and the places of spending them were examined in accordance with the archive documents. The socio-economic status of Mihrişah Valide Sultan has been tried to be revealed through the expenditures she made for herself, her employees, the dynasty, the poor and the state. However, it has been tested whether there is a personality as it is said in the literature. Thus, it was aimed to shed light on the lives of other valide sultans, especially Mihrişah Valide Sultan. The study covers the income expenses of Mihrişah Valide Sultan for about eight years (1213-1220/1798-1805). However, the 21 month expense records during this period could not be reached. As a result, it was understood that the valide sultan was elegant as well as being kind, benevolent and religious. In this context, it can be said that he uses a large part of his income for charity and spends the rest of his income for the place and clothing he lives in. During the period in question, he did not take any debt, although he made a loan. It is possible to say that he made great efforts for the continuation of the Ottoman dynasty and was a supporter of his son in every way. In addition, it can be claimed that he performed religious, customary and harem ceremonies within the framework of the rules of ceremony, similar to the sultan.

Sultan III. Mustafa’nın (1757-1774) başkadını ve Sultan III. Selim’in (1789-1807) de annesi olan Mihrişah, Osmanlı Devleti’nde 1789-1805 yılları arasında valide sultanlık yapmıştır. Mihrişah padişahtan sonra en fazla gelire sahip olmuştur. O, literatürde daha çok “nazik, hayırsever ve dindar” olarak tanıtılmıştır. Genelde yaptığı hayratla anılmıştır. Bu çalışma ile valide sultanın, vakıf gelirleri ve giderleri dışında, has gelirleri ve bunları harcama yerleri arşiv belgeleri doğrultusunda incelenmiştir. Mihrişah’ın kendisi, çalışanları, hanedan çevresi, fakirler ve devlet için yaptığı harcamalar üzerinden sosyo ekonomik durumu ortaya çıkarılmaya çalışılmıştır. Literatürde denildiği gibi bir şahsiyet olup olmadığı test edilmiştir. Mihrişah özelinde diğer valide sultanların hayatına da ışık tutulmak istenmiştir. Çalışma, Mihrişah’a ait 1213-1220/1798-1805 arasına tarihlenen yaklaşık sekiz yılın, 21 ay hariç, gelir giderlerini kapsamaktadır. Mihrişah’ın gelirini harcadığı yerlere ve harcama tercihlerine bakarak onun nazik, dindar ve hayırsever kişiliğinin yanında zarif de olduğu iddia edilebilir. Bu çerçevede gelirinin büyük bir bölümünü hayrat için kullandığı, kazancının kalanıyla da bulunduğu mekân ve giyim kuşamı için harcama yaptığı söylenebilir. Söz konusu dönemde borç verdiği halde herhangi bir borç almamıştır. Osmanlı hanedanın devamı için çok çaba sarfettiğini ve oğlunun her yönden destekçisi olduğunu söylemek mümkündür. Ayrıca özellikle dinî, örfi ve hareme ait törenleri teşrifat kuralları çerçevesinde, padişaha benzer şekilde, yaptığı iddia edilebilir.
MİHRİŞAH VALİDE SULTAN’IN 1798-1805 YILLARI ARASI HAS GELİRLERİ VE HARCAMALARI